Shaping an attractive image of an employer: reaching Lithuania’s gen Y specialists - Žarnauskaitė, Milda (Information & Media, 2017)
Compared with older generations, Gen Y’s expectations for an attractive workplace are different. The Millennials demonstrate higher levels of engagement in technology, which affects their communication habits. Because of this, to attract specialists representing Gen Y, organizations should take into account what Gen Y expects from an attractive workplace and what manners of communication the representatives of this generation prefer. Any empirical research or studies regarding the expectations that millennials have for an attractive employer and for employer branding communication in Lithuania are scarce. This paper is aimed at determining the peculiarities of employer branding, focusing on specialists representing the Millennials, or Generation Y, in Lithuania. To reach the aim, the following steps were taken: the process of employer branding for potential employees was analyzed; factors in determining an employer’s attractiveness (taking generational differences into account), were determined; peculiarities of employer branding, focusing on professionals representing Gen Y in Lithuania, were investigated. Data was collected by conducting semi-structured, in-depth interviews. The data was analyzed inductively, using the thematic analysis method. The research revealed that the most important factors in determining employer attractiveness, were the symbolic employer image attributes, representing interest and social values. The most effective channels in establishing contact with Millennial professionals were determined to be social media networks Facebook and LinkedIn. After the initial contact, the main source of information about an employing company was determined to be its website. An analysis of the data revealed that the visualization and personification of communication were preferred.
Keywords: ...